Karakteristik Organoleptik Permen Jeli Sari Kacang Merah dengan Penambahan Gelatin Tulang Ikan Nila Merah - Iswahyudi, Iswahyudi; Nuraida, Nisa; Putri, Imawati E (AGRITEKNO: Jurnal Teknologi Pertanian, 2023)
This study aimed to determine the organoleptic characteristics of red bean extract based on jelly candy with the addition of nile bones gelatin. This study used a completely randomized design with factorial experiments. The first factor is Nila-bones gelatin concentration which consists of concentration levels A1 (10 g) and A2 (13 g). The second factor was the addition of red bean extract to replace water which consisted of 3 levels, namely B1 (50%), B2 (70%), and B3 (100%). Data analysis of organoleptic used the Kruskal-Wallis test. When p < 0.05, will be continued by the Mann Whitney test at the real level α 5%. The results showed that the addition of Nila-bones gelatin to jelly candy based on red bean extract had a significant effect (p < 0.05) on the quality and level of overall panelist preference. A1B2 (10 g of gelatin; 70% of red bean extract) is the formula for the selected jelly candy red bean extract.